Automatically Provisioned Embedded Communication System Based on Openwrt Platform - Slachta, Jiri; Voznak, Miroslav; Komosny, Dan; Toral-Cruz, Homero; Fazio, Peppino (Communications - Scientific letters of the University of Zilina, 2016)
The article deals with a design of a system that provides tools for creation of automatically provisioned embedded communication system and its components. As the key feature of the BEESIP platform (Bright Efficient Embedded Solution for IP Telephony) a unique building and provisioning system of the network devices has been developed allowing the administrators to fully control the firmware and configuration of the devices even in the remote and inaccessible locations. The process of custom firmware building and device provisioning eases the mass deployment of the BEESIP based hardware to cover the needs of small to medium business in the vast range of services.